Adjusted estimate of the prevalence of hepatitis delta virus in 25 countries and territories - Razavi-Shearer, D.; Child, H.; Voeller, A.; Buti, M.; Tacke, F.; Terrault, N.; Zeuzem, S.; Abbas, Z.; Akarca, U.S.; Al Masri, N.; Alalwan, A.; Blomé, M. Alanko; et al. (Journal of hepatology, 2024)
Hepatitis delta virus (HDV) is a satellite RNA virus that requires the hepatitis B virus (HBV) for assembly and propagation. Individuals infected with HDV progress to advanced liver disease faster than HBV-monoinfected individuals. Recent studies have estimated the global prevalence of anti-HDV antibodies among the HBV-infected population to be 5-15%. This study aimed to better understand HDV prevalence at the population level in 25 countries/territories. We conducted a literature review to determine the prevalence of anti-HDV and HDV RNA in hepatitis B surface antigen (HBsAg)-positive individuals in 25 countries/territories. Virtual meetings were held with experts from each setting to discuss the findings and collect unpublished data. Data were weighted for patient segments and regional heterogeneity to estimate the prevalence in the HBV-infected population. The findings were then combined with The Polaris Observatory HBV data to estimate the anti-HDV and HDV RNA prevalence in each country/territory at the population level. After adjusting for geographical distribution, disease stage and special populations, the anti-HDV prevalence among the HBsAg+ population changed from the literature estimate in 19 countries. The highest anti-HDV prevalence was 60.1% in Mongolia. Once adjusted for the size of the HBsAg+ population and HDV RNA positivity rate, China had the highest absolute number of HDV RNA+ cases. We found substantially lower HDV prevalence than previously reported, as prior meta-analyses primarily focused on studies conducted in groups/regions that have a higher probability of HBV infection: tertiary care centers, specific risk groups or geographical regions. There is large uncertainty in HDV prevalence estimates. The implementation of reflex testing would improve estimates, while also allowing earlier linkage to care for HDV RNA+ individuals. The logistical and economic burden of reflex testing on the health system would be limited, as only HBsAg+ cases would be screened. There is a great deal of uncertainty surrounding the prevalence of hepatitis delta virus among people living with hepatitis B virus at the population level. In this study, we aimed to better understand the burden in 25 countries and territories, to refine techniques that can be used in future analyses. We found a lower prevalence in the majority of places studied than had been previously reported. These data can help inform policy makers on the need to screen people living with hepatitis B virus to find those coinfected with hepatitis delta virus and at high risk of progression, while also highlighting the pitfalls that other researchers have often fallen into. [Display omitted] •Previous studies have focused on the risk groups and regions that carry the highest HDV burden.•HDV prevalence among people living with HBV in 25 countries/territories was often (18/25) lower than previous estimates.•The highest prevalence was in Mongolia, but the largest absolute number of HDV-RNA+ individuals was in China.